Shapers of the great debate on the Civil War : a biographical dictionary - Monroe, Dan, 1961- (Shapers of the great American debates, 2005)
With the conclusion of the Mexican War in 1848, the United States seemed poised to fulfill the manifest destiny that was on the lips of journalists and politicians. Yet, even before the war was over, tensions over the issue of slavery erupted. Slavery symbolized the social, cultural, constitutional, and economic differences that were dividing the North and South. Through four years of bloody civil war and the loss of over 600,000 lives, the American republic decided the fate of slavery, asserted the supremacy of the federal government over state authority, and began to grapple with the difficu.